The intention-behavior gap in climate change adaptation - Martin Kesternich; Daniel Osberghaus; W. J. Wouter Botzen (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2022)
Most empirical studies on private climate change adaptation rely on self-reported intentions which often fail to translate into real actions. Consequently, this strand of literature can only insufficiently account for the intention behavior gap (IBG) in climate change adaptation, which complicates the deduction of policy recommendations for stimulating adaptation behavior. Using a large unique longitudinal survey data set from Germany covering more than 5,000 households, our study offers extensive insights into the IBG in climate change adaptation by analyzing intentions and actual implementations of both flood-proofing and heat stress reduction measures. Our results do not only reveal a substantial IBG for most stated intentions but also show that intentions can rarely serve as good predictors for realized actions. At the same time, the IBG itself can hardly be explained by observable household data characteristics which in turn again makes it difficult to reveal information on realized actions out of stated intentions only. However, we also find that drivers of adaptation intentions are often reasonable proxies for assessing the drivers of behavior. This implies that similar explanatory variables affect both intentions and implementations, but they provide only limited insights on the actual levels of implemented intentions. In line with regret theory, the IBG in our data can be partly explained by anticipated regret caused by a feeling of having invested in vain in cases where adaptation measures are installed but extreme weather events do not occur for the time being.
Keywords: Q54; D91; 330; Intention-behavior gap; Adaptation; Climate Change; Flooding; Heat